Application of Very Urgent Criteria in The Marriage Dispensation Norms for the Protection of Children: Analysis of Jasser Auda's Theory - Asmuni, Asmuni; Rezha Nur Adikara , Rezha Nur Adikara (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
The renewal of marriage legal norms regarding the minimum age limit for marriage with the criteria of